Strategi Pemasaran Oleh Rumah Sakit Melalui Penyelenggaraan Medical Tourism - Budi Prabowo (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Emerging global competition in the industry of health is possible for patients from the country more proceed On do journey to a country to develop by getting maintenance quality medical _ tall And with affordable prices. _ Medical Tourism as part of Strategy Marketing House Sick in the Tourism Area. Writing This explains Medical Tourism and strategy marketing hospital in Indonesia. Study This aim is to analyze the readiness of House Sick, government, and travel agency tours in service tour medical. House Sick as a business private use various strategy For interesting more Lots patient or customers, like creating room therapy in a hybrid hotel (home-designed pain _ For comfort patient international ). House Sick Also compile strategy marketing For direct patient And customer as well as identify three strategies the is with connect to patient potential through a visit to the country origin, employ intermediary journey medical And compile 'medical check-up' package for person healthy.